MARINE COPERNICUS OCEANOGRAPHIC DATA ANALYSIS: A COMPARATIVE STUDY WITH BUOY RAMA MEASUREMENTS - Nurzeha, Ridwan; Lumban-Gaol, Jonson; Bahri Agus, Syamsul (Politeknik Kelautan dan Perikanan Dumai, 2025)
Oceanographic data such as Sea Surface Temperature (SST), Sea Surface Salinity (SSS), and Sea Surface Height (SSH) have a significant role in understanding ocean related studies, such as fisheries and ocean biology. This study analyzed the accuracy of Marine Copernicus datasets by comparing with data from buoy RAMA in the Indian Ocean. The results show a strong correlation for SST (r=0.988, R2=0.976, bias -0.020, RMSE 0.110) and SSS (r=0.960, R2=0.921, bias -0.001, RMSE 0.119). For SSH, after correction also has strong correlation with lower bias (r=0.934, R2=0.872, bias -0.000, RSME 0.032). The seasonal trend analysis shows SST peaks in April-May and declines to its lowest in September, while salinity increases from April to July-August before decreasing. SSH has a rising trend from January to June and declines afterward. These findings suggest that Marine Copernicus data provide reliable SST, SSS, and SSH estimates.